PENGARUH PENGETAHUAN PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KECAMATAN MAUK - Seftiyanti, Shufi; Benarda (Publika Citra Media, 2025)
His study aims to see the effect of tax knowledge and taxpayer awareness on taxpayer compliance in paying land and building tax in Mauk District with a quantitative approach. The population of the study was land and building taxpayers registered in Mauk District. Primary data was obtained through questionnaires to respondents. Samples were taken using the convenience sampling method using the Slovin formula, resulting in 99 samples. Data analysis used multiple linear regression with SPSS version 25. The results showed that the effect of tax knowledge had a positive effect on taxpayer compliance, and taxpayer awareness also had a positive effect on taxpayer compliance.